Paracetamol, NSAIDS and opioid analgesics for chronic low back pain: a network meta‐analysis - Bagg, Matthew K (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To answer the clinical question: ‘what analgesic medicine shall I prescribe this patient with chronic low back pain to reduce their pain?’. The objectives are to determine the analgesic effects, safety, effect on function, and relative rank according to analgesic effect, safety and effect on function of a single course of opioid analgesics, NSAIDs or paracetamol or combinations of these medicines.